Determination of Size of the Chromate Ion-A Solvent Extraction Study - Rao, V.M.; Kuntam Raju, A. (Asian Journal of Chemistry, 2010)
The extraction of Cr(VI) into benzene solutions of Aliquot-336 has been studied from chloride, bromide and nitrate systems and the extracted species has been determined. An attempt is made to determine the size of the anion of chromium(VI) (i.e. HCrO4–) from the distribution data. Experimentally determined values of the size of the ion are comparable with those obtained by theoretical calculation.